2018
DOI: 10.1073/pnas.1807319115
|View full text |Cite
|
Sign up to set email alerts
|

The mutagen and carcinogen cadmium is a high-affinity inhibitor of the zinc-dependent MutLα endonuclease

Abstract: SignificanceMutLα (MLH1-PMS2 heterodimer) is an endonuclease that acts during an early step of eukaryotic mismatch repair. We show that human MutLα endonuclease copurifies with two equivalents of bound zinc, at least one of which resides within the endonuclease active site. We also show that cadmium, a known inhibitor of zinc-dependent enzymes and a potent mutagen and carcinogen, is a high-affinity inhibitor of MutLα endonuclease and that exogenous MutLα significantly reverses the mismatch repair defect in cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
(89 reference statements)
1
19
0
Order By: Relevance
“…We refined our prior algorithm (Ayaz et al , 2014; Piedra et al , 2016; Mickolajczyk et al , 2018) that used a kinetic Monte Carlo algorithm (Gillespie, 1976; Gibson and Bruck, 2000) to simulate microtubule dynamics. The algorithm simulates one biochemical event (dimer association, dissociation, or GTP hydrolysis) at a time and therefore provides a “movie”’ of microtubule dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We refined our prior algorithm (Ayaz et al , 2014; Piedra et al , 2016; Mickolajczyk et al , 2018) that used a kinetic Monte Carlo algorithm (Gillespie, 1976; Gibson and Bruck, 2000) to simulate microtubule dynamics. The algorithm simulates one biochemical event (dimer association, dissociation, or GTP hydrolysis) at a time and therefore provides a “movie”’ of microtubule dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…In these kinds of models, catastrophe and rescue occur naturally (Figure 1C) in a way that depends on the specific parameters used. Our algorithm is constructed in a highly modular way that makes it easy to implement different biochemical assumptions (Piedra et al , 2016; Mickolajczyk et al , 2018). Later in the paper, we relax the minimalistic assumptions of the two-state model to test whether more complicated models that incorporate other states or kinds of biochemistry better predict the concentration dependence of catastrophe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have identified several molecular processes that are dysregulated by Cd exposure. These include induction of oxidative stress, inhibition of apoptosis and DNA repair process (Sherrer et al, 2018). In addition, dysregulation of epigenetic processes including DNA methylation and histone acetylation causing aberrant gene transcription has been associated with Cd exposure (Park et al, 2017;Peng et al, 2019;Wang and Yang, 2019).…”
Section: Introductionmentioning
confidence: 99%